Viability and storability of mango (Mangitera indica) seeds. - Dujale, Maria Abigail (Iloilo City UPHSI, 2001)
Mangoes (Mangifera indica) are trees abundant in tropical areas, which can be grown through seed-planting. Its fruit is the third most leading fruit export in the Philippines. The study aimed to 1) know the viability of mango seeds after storage at different time intervals, 2) determine the storage duration that would result to earliest germination, 3) compare the growth rates of shoots from seeds stored at different time intervals. Mangifera indica were planted to determine the percent viability of the seeds and the mean growth rate at different time intervals. The storage time intervals were 2 days, 4 days, 6 days, and 8 days after the control treatment was planted. The seeds were planted in soil bags, randomly distributed inside an improvised greenhouse and watered daily. The results showed that Mangifera indica seeds with storage time of 2 days and 8 days obtained the highest viability of 70%. Fastest mean germination time of 12 days was obtained by seeds with storage time of 6 days. One-way Analysis of Variance at 0.05 showed that there was a significant difference in the mean germination time and mean growth rates in terms of mean height, mean diameter, and mean number of leaves of the different treatments.
Research II : Research Manuscripts
Keywords: Mango seeds